Hydrothermal alteration and lithogeochemistry of the Boundary volcanogenic massive sulphide deposit, central Newfoundland, Canada - Buschette, Michael J.; Piercey, Stephen J. (Canadian Journal of Earth Sciences, 2016)
The Boundary volcanogenic massive sulphide deposit (0.50 Mt at 3.5% Cu, 4.0% Zn, and 1.0% Pb, 34 g/t Ag) is hosted by the Tally Pond group (∼510 Ma), Victoria Lake supergroup, central Newfoundland, Canada, and represents a subseafloor replacement-style massive sulphide deposit. The deposit is hosted by rhyolitic lapilli tuff of the Bindons Pond formation. The rhyolites have immobile element signatures consistent with the formation of felsic rocks through the melting of juvenile-weakly evolved crust within an extensional rift environment (rifted peri-continental arc). The host rocks of the Boundary deposit contain elevated alteration indices, including high Ba/Sr, Hg/Na 2 O, chlorite–carbonate–pyrite index, and Ishikawa alteration index values. The mobile element geochemistry effectively differentiates between three distinct hydrothermal alteration styles: intense chlorite, chlorite-sericite, and quartz-sericite. Intense chlorite alteration exhibits mass gains in MgO and Cu and depletions in K 2 O and Ba. Chlorite-sericite alteration contains variable gains and losses of SiO 2 , K 2 O, Ba, MgO, and Fe 2 O 3 depending on the dominant matrix mineral phase (i.e., chlorite vs. sericite). The quartz-sericite assemblage has mass gains in SiO 2 , K 2 O, Ba, and Fe 2 O 3 . Short-wave infrared spectroscopic data, particularly AlOH and FeOH absorption hulls, differentiate alteration styles and correlate with lithogeochemical results: AlOH absorption features increase in length (>2208 nm) proximal to Zn mineralization and wavelength variations correspond to relative abundances of sericite and chlorite. Electron probe microanalyses indicate that increasing short-wave infrared wavelengths correlate with increasing Mg–Fe and Fe contents in sericite and chlorite, respectively. Collectively, these data have been used to develop a three-dimensional alteration model of the Boundary deposit.